Experiences Of Foreign Tourists In The Old City Of Semarang: Evaluation Of Service Quality Foreign Languages In The Tourism Context - Henry Yuliamir; Enik Rahayu; Renny Aprilliyani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Research aims to evaluate the quality of foreign language services provided to foreign tourists visiting the Old City of Semarang, a tourism destination that is increasingly in demand. This research uses a qualitative approach with various methods, including case studies, indepth interviews with foreign tourists, content analysis, participant observation, document analysis and data triangulation. The research results revealed that the majority of foreign tourists were impressed with foreign language services in the Old City of Semarang. They shared positive stories about interactions with officers who tried to help in a foreign language, which made them feel welcome and comfortable. Another positive experience involves the ability to explore the culture and history of the city through smooth interactions with local residents who are fluent in foreign languages. However, a number of foreign tourists also face obstacles, especially in terms of communication, navigation and understanding cultural differences. Some of the recommendations given by foreign tourists include increasing language training for officers, providing more information materials in foreign languages, improving navigation, cultural exchange programs, use of technology, tourist feedback channels, and increasing cooperation between stakeholders. This research has important implications for improving the tourism sector and local economy. Improving foreign language services in the Old City of Semarang can increase tourist satisfaction, result in repeat visits, positive recommendations, and a positive contribution to the city's economic growth. Therefore, language training, provision of information materials, improved navigation, promotion of culture, technology, feedback channels, and cooperation between stakeholders are key steps in achieving this goal.